Boosting bifunctional oxygen electrocatalysis with 3D graphene aerogel-supported Ni/MnO particles - Fu, Gengtao (2020)
Electrocatalysts for oxygen-reduction and oxygen-evolution reactions (ORR and OER) are crucial for metal-air batteries, where more costly Pt- and Ir/Ru-based materials are the benchmark catalysts for ORR and OER, respectively. Herein, for the first time Ni is combined with MnO species, and a 3D porous graphene aerogel-supported Ni/MnO (Ni-MnO/rGO aerogel) bifunctional catalyst is prepared via a facile and scalable hydrogel route. The synthetic strategy depends on the formation of a graphene oxide (GO) crosslinked poly(vinyl alcohol) hydrogel that allows for the efficient capture of highly active Ni/MnO particles after pyrolysis. Remarkably, the resulting Ni-MnO/rGO aerogels exhibit superior bifunctional catalytic performance for both ORR and OER in an alkaline electrolyte, which can compete with the previously reported bifunctional electrocatalysts. The MnO mainly contributes to the high activity for the ORR, while metallic Ni is responsible for the excellent OER activity. Moreover, such bifunctional catalyst can endow the homemade Zn-air battery with better power density, specific capacity, and cycling stability than mixed Pt/C + RuO2 catalysts, demonstrating its potential feasibility in practical application of rechargeable metal-air batteries.